Single-Molecule Test for Markovianity of the Dynamics along a Reaction Coordinate - Berezhkovskii, Alexander M. (J Phys Chem Lett, 2018)
In an effort to answer the much-debated question of whether the time evolution of common experimental observables can be described as one-dimensional diffusion in the potential of mean force, we propose a simple criterion that allows one to test whether the Markov assumption is applicable to a single-molecule trajectory x(t). This test does not involve fitting of the data to any presupposed model and can be applied to experimental data with relatively low temporal resolution.